Effect of Invasive Aquatic Plants (Azolla a., Myriophyllum a. and Cyperus a.) Biochar Amendment on Maize Growth: An Assessment - Ouédraogo, Sidbe Wendin Nestor; Komoe, Koffi; Lompo, Désiré Jean Pascal; Da, Sié Sylvestre; Isimemen, Osemwegie; Masse, Dominique (Journal of Agricultural Studies, 2021)
The management of invasive aquatic plants (IAPs), which is primarily accomplished through manual grubbing, incurs significant costs for populations, especially since the operations must be renewed on a regular basis. Converting IAPs into biochar for use as soil amendment will help offset the costs of this mechanical control strategy, while also improving carbon sequestration, soil fertility and crop yields. The objective of this study is to examine the effects of using IAPs biochar amendment on the quality of acidic soils and subsequently maize growth. Ten treatment groups including nine treatments and one control were established with four replicates each on freshly sown maize soils. Treatments options include applying IAP biochar (group 1), different combinations of IAP biochar and poultry manure (group 2), and mineral fertilizer (group 3). After 37 days, the average height of maize plants in the control group is 68.83±7.91cm, compared to 69.82 ± 7.34 cm (group1), 64.44 ± 7.82cm (group 2) and 69.08 ± 9.51cm (group 3). Multivariate analyses suggest that the IAPs biochar have significantly higher potential to improve plant growth parameters than either poultry manure or synthetic fertilizer. Based on the foregoing, the use of IAPs biochar amendment should be promoted among smallholder farmers because it is environmentally friendly, easy to produce, has a lower operational cost than other fertilizers, and has been shown to improve the acidic and impoverished dryland soils prevalent in Burkina Faso.